The Reconstruction of Korean Wave in Indonesian Fan Fiction - Dyah Raina Purwaningsih; Aidatul Chusna (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2013)
Recently, literary world is enriched by the emergence of a new form of fiction called fan fiction, which refers to a fictional writing produced by fan writers as an expression of love towards their idolized stars. The emergence of fan fiction in Indonesia recently is in line with the attack of Korean wave or Hallyu to Indonesian showbiz. This article is talking about Indonesian Korean fan fiction reconstruction based on several approaches proposed by Jenkins (1992). The approaches, which cover recontextualization, expanding the series timeline, refocalization, moral alignment, genre shifting, cross-over, character dislocation, personalization, emotional intensification, and eroticization, are used as the ways to guide fan writers in reconstruct a story about an idol that cannot be found in real life. Using those approaches, a fan writer can freely express their adoration toward the figures they idolize. This article aimed at specifically cutting open some Indonesian fan fictions entitled “Tormented”, “Wonder Boy”, and “Way Back into Love”, based on Jenkin’s approaches, using descriptive qualitative research method. The analysis shows that there are six approaches used by the writers in reconstructing the stories; refocalization, moral alignment cross-over, character dislocation, personalization, and eroticization.